Antenna Design for Microwave and Millimeter Wave Applications II: Latest Advances and Prospects - Hosung Choo (Applied Sciences, 2022)
In recent decades, novel and significant approaches to the design of antennas for various microwave and millimeter-wave applications have been attempted [...]